Performance analysis of free space optical links using multi‐input multi‐output and aperture averaging in presence of turbulence and various weather conditions. Issue 8 (1st May 2015) - Kaur, Prabhmandeep; Jain, Virander Kumar; Kar, Subrat
Abstract : The authors study the effect of multi‐input multi‐output (MIMO) spatial diversity schemes when used in a free space optical (FSO) communication link in the presence of turbulence and varied weather conditions such as very clear air, drizzle, haze, fog etc. The performance is evaluated in terms of the bit error rate (BER) and outage probability P out . We show that MIMO schemes cause a decrease in the BER and P out which, at low signal‐to‐noise ratios, is more significant in presence of very clear air and clear air as compared with haze and fog weather conditions. The diversity gain at a BER of 10 −6 is evaluated and observed to increase as the number of transmit/receive apertures increase. However, it remains almost constant over all the weather conditions for a given MIMO scheme and turbulence strength. The performance of FSO link with MIMO schemes is compared with a FSO link using aperture averaging. Owing to constraint on the receiver aperture diameter, the aperture averaging technique fails to give the same kind of performance as provided by the higher order MIMO schemes.